A9.1 Macrophage activation syndrome after mycoplasma pneumoniae infection. (31st January 2014) - Szolga, Blanca; Filipescu, Ileana; Damian, Laura; Rednic, Simona; Rednic, Nicolae
Abstract : Introduction: Macrophage activation syndrome is a rare and potentially life threatening condition, triggered by various events like bacterial and viral illness and sometimes it can be a complication of childhood rheumatic disorders. Physical and laboratory results usually show non-remitting fever, hepatosplenomegaly, lymphadenopathy, bleeding diathesis, altered mental status, rash, pancytopenia and impaired liver and renal function tests, elevated triglyceride and serum ferritin levels. Corticosteroids and Cyclosporine are the drugs commonly used in its management. Early diagnosis and prompt treatment can be life saving. Objective: To present a case of Macrofage activation syndrome triggered by a Mycoplasma pneumoniae infection. Background: A 18 years old male pacient presented with high fever, tachycardia, lethargy, leucopenia and artharlgias after having a Mycoplasma pneumoniae infection treated in the Infectious disease department. Investigations: Physical and laboratory results showed hepatosplenomegaly, high fever, tachycardia, low levels of Ig G and Ig M, leucopenia and the bone marrow aspiration showed cells phagocytosing hematopoietic elements. Also, on the basis of the effectuated investigations ( CBC; biochemistry and immunology tests; cultures of boold, urine, stool; abdomen and heart ultrasonography; thoracic CT) other infectious, malignant or rheumatic diseases were exclused. Diagnosis: Macrophage activation syndrome triggered by a Mycoplasma pneumoniae infection. Management: The patient's disease was successfully controlled following the treatement with Methyprednisolone and Cyclosporine. Discussion and conclusion: This case illustrates this rare, but potentially life-threatening condition sometimes associated with chronic rheumatic disorders with various triggering events like bacterial and viral illness. Differentiation from a disease flare of a rheumatic disorder is difficult and that is why pacients with this condition need further investigation and careful monitoring. In conclusion, MAS is a severe, potentially life-threatening complication of chronic rheumatic disease; therefore it is essential for clinicians to have a high threshold of suspicion, make an early diagnosis, and start prompt treatment to have success.